COMPARISON OF SERUM VITAMIN A LEVELS BETWEEN NEONATES WITH CONGENITAL HEART DISEASE AND CONTROLS - Abtahi, Saeed; Mostafavian, Zahra; Behnam, Babak; Shaye, Zahra Abbasi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Prevention of congenital heart disease (CHD) has been hampered by a lack of information about the known modifiable risk factors for abnormalities in cardiac development. Vitamin A plays an important role in the periods of rapid cellular growth and differentiation, especially during pregnancy. Assuming a link between Vitamin A levels and congenital malformations, hypothetical different levels of Vitamin A were evaluated in neonates with and without CHD, in this study. Methods: In a case–control study that was conducted in 2015 in Mashhad/Iran, serum levels of Vitamin A in 30 neonates with CHD were compared to 30 healthy controls. The cases were diagnosed by echocardiography and recruited by convenience sampling. Demographic and laboratory data including age, sex, and serum Vitamin A level in each group were collected. Data analysis was done in SPSS V 20 software, and descriptive statistics, t-test, and analysis of covariance were used. Results: The mean age in cases was 11±3.4 days and in controls was 12.5±4.8 days. A total of 18 patients (60%) were male. In CHD patients, 10 cases (33.3%) had cyanotic heart disease, and 20 cases (66.7%) had non-cyanotic heart disease. The mean serum Vitamin A values in subjects (11.54±9.56 μg/dL) and controls (21.84±14.3 μg/dL) were significantly different, (p<0.05) and in case group was lower than the normal range. Conclusion: There was a significant difference in serum Vitamin A values in subjects and controls. Therefore, awareness of people about the importance of this vitamin in preventing CHD in children seems necessary.